PENERAPAN TEKNIK PROGRESSIVE MUSCLE RELAXATION DALAM MENINGKATKAN KONSENTRASI BELAJAR SISWA - Azizah Azizah; Aida Imtihana; Ibnu Rozali (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. The background of this study focuses on the low level of students’ learning concentration caused by academic pressure, environmental distractions, and individual factors. The main problem addressed in this research is the students’ weak ability to maintain attention during the learning process. The purpose of this study is to determine the effect of applying the Progressive Muscle Relaxation technique on improving students’ learning concentration, with the expectation of contributing to the development of effective learning strategies that enhance focus and academic achievement. The method used in this study was a quantitative approach with a Pre-Experimental design, specifically the One Group Pretest-Posttest Design. The research sample consisted of 32 students selected through purposive sampling. Data were collected using a learning concentration questionnaire and analyzed using the Paired Sample t-Test to test the established hypothesis. The validity and reliability of the instrument were examined using the Product Moment correlation and Cronbach’s Alpha formula. The results of statistical analysis showed an increase in students’ learning concentration after the implementation of the Progressive Muscle Relaxation technique, as indicated by the average posttest score of 54.00, which was higher than the pretest score of 50.47. The two-tailed hypothesis test revealed that the tcount value (-4.47) was within the hypothesis acceptance region (tcount -4.47 > ttable 2.04) with a significance value of 0.00 < 0.05. Thus, it can be concluded that the Progressive Muscle Relaxation technique is effective in improving students’ learning concentration, indicating that the hypothesis (Hα) is accepted. This study provides a practical contribution to the development of teaching methods that emphasize the balance between physical relaxation and mental readiness to support academic success. Keywords: Progressive Muscle Relaxation, Improvement, Learning concentration, Students Abstrak. Latar belakang penelitian ini berfokus pada rendahnya konsentrasi belajar siswa yang disebabkan oleh tekanan akademik, gangguan lingkungan, dan faktor individu. Masalah utama yang dibahas dalam penelitian ini adalah lemahnya kemampuan siswa untuk mempertahankan perhatian selama proses belajar. Tujuan penelitian ini adalah untuk mengetahui pengaruh penerapan teknik Relaksasi Otot Progresif terhadap peningkatan konsentrasi belajar siswa, dengan harapan dapat berkontribusi pada pengembangan strategi belajar efektif yang meningkatkan fokus dan prestasi akademik. Metode yang digunakan dalam penelitian ini adalah pendekatan kuantitatif dengan desain Pra-Eksperimental, khususnya Desain Pretest-Posttest Satu Kelompok. Sampel penelitian terdiri dari 32 siswa yang dipilih melalui purposive sampling. Data dikumpulkan menggunakan kuesioner konsentrasi belajar dan dianalisis menggunakan Uji t Sampel Berpasangan untuk menguji hipotesis yang telah ditetapkan. Validitas dan reliabilitas instrumen diperiksa menggunakan korelasi Product Moment dan rumus Alpha Cronbach. Hasil analisis statistik menunjukkan peningkatan konsentrasi belajar siswa setelah penerapan teknik Relaksasi Otot Progresif, yang ditunjukkan oleh nilai rata-rata posttest sebesar 54,00, yang lebih tinggi dari nilai pretest sebesar 50,47. Uji hipotesis dua arah mengungkapkan bahwa nilai t hitung (-4,47) berada dalam wilayah penerimaan hipotesis (t hitung -4,47 > t tabel 2,04) dengan nilai signifikansi 0,00 < 0,05. Dengan demikian, dapat disimpulkan bahwa teknik Relaksasi Otot Progresif efektif dalam meningkatkan konsentrasi belajar siswa, yang menunjukkan bahwa hipotesis (Hα) diterima. Studi ini memberikan kontribusi praktis terhadap pengembangan metode pengajaran yang menekankan keseimbangan antara relaksasi fisik dan kesiapan mental untuk mendukung keberhasilan akademik. Kata kunci: Progressive Muscle Relaxation, Peningkatan, Konsentrasi belajar, Siswa.